Insulin‐like growth factor‐1 predicts cognitive functions at 2‐year follow‐up in early, drug‐naïve Parkinson's disease. (29th March 2013) - Pellecchia, M. T.; Santangelo, G.; Picillo, M.; Pivonello, R.; Longo, K.; Pivonello, C.; Vitale, C.; Amboni, M.; De, A.; Moccia, M.; Erro, R.; De, G.; et al.
<x xml:space="preserve">Abstract</x> Background and purpose Cognitive impairment is common in Parkinson's disease (PD), even in the early stages. We aimed to assess the relationship between insulin‐like growth factor‐1 (IGF‐1) and cognitive functions in early, drug‐naïve patients with PD. Methods Serum IGF‐1 was measured in 65 early, drug‐naïve patients with PD that underwent a complete neuropsychological battery at baseline and after 2 years. Linear regression analysis was used to evaluate the relationships between neuropsychological scores and IGF‐1. Repeated‐measures anova was applied to assess changes in neuropsychological variables over time. Results At baseline, IGF‐1 levels were related to phonological fluency. At follow‐up, IGF‐1 levels were associated with the Rey auditory verbal learning test (RAVLT) – immediate and delayed recall, Frontal Assessment Battery, verbal span and Benton judgement of the line orientation test. Patients with low IGF‐1 levels at baseline showed a significantly faster decline of performances than patients with high IGF‐1 levels on immediate and delayed recall of the RAVLT and interference task of the Stroop test. Conclusions Low serum IGF‐1 levels are related to poor performance on executive tasks in early, drug‐naïve patients with PD, and may predict poor performance on attention/executive and verbal memory tasks after a 2‐year follow‐up.